DISINFECTANT MAKING TRAINING FOR MICRO-ENTREPRENEUR HOUSEWIVES GROUP ASSISTED BY THE BANDA ACEH CITY COOPERATIVE OFFICE - Sayed Rahmad Aulia (CV. Naskah Aceh, 2024)
Since the advent of covid-19, hand sanitizers and disinfectants have become essential today. Disinfectants can kill germs or coronaviruses that stick to inanimate objects such as tables, chairs, or other inanimate objects. Therefore, the purpose of community service activities carried out by the service team is to provide an understanding of the importance of maintaining covid 19 transmission and providing skills in making disinfectants using materials commonly used in households, such as floor cleaners, clothes bleach and other antiseptics. The service activity model is empowerment with a method of skill development through training. The results of the activity show that the participants have understood the material that has been provided and the participants have been able to make and practice how to make disinfectants from the ingredients that have been practiced with an understanding level of 76 percent, where participants are expected to be able to apply the material in their daily lives without having to buy it outside, so as to save household expenses. Through questionnaires collected from the training participants, a list of training needs for business development was generated, such as access to cheap raw materials, capital, marketing, and training on how to market online.